Efficacy of Flavonoids in Combating Fluconazole Resistant Oral Candidiasis - Srivastava, Dipti; Yadav, Aarti; Naqvi, Salma; Awasthi, Himani; Fatima, Zeeshan (Current Pharmaceutical Design, 2022)
Background: Candida is an opportunistic fungus often present in the oral mucosa. In the compromised immune system, it may become pathogenic and cause oral candidiasis. This infection is more common with Candida albicans; though, non-albicans Candida spp also have significant relevance. Current treatment guidelines include polyenes, azoles and echinocandins, where fluconazole is the primary therapeutic option. However, both inherited and acquired resistance to fluconazole is exhaustively reported. The development of resistance has resulted in the worsening of the original and re-emergence of new fungal diseases. Thus, the development of an anti-candidiasis therapy with a satisfactory outcome is the urgent need of the hour. Objective: This review article aims to stimulate research in establishing the synergistic efficacy of various flavonoids with fluconazole to combat the resistance and develop an effective pharmacotherapy for the treatment of oral candidiasis. Further, in this article, we discuss in detail the mechanisms of action of fluconazole, along with the molecular basis of the development of resistance in Candida species. Methods: PubMed and other databases were used for literature search. Results: The designing of natural drugs from the plant-derived phytochemicals are the promising alternatives in modern medicine. The challenge today is the development of alternative anti-oral candidiasis drugs with increased efficacy, bioavailability and better outcome which can combat azole resistance. Identifying the flavonoids with potential antifungal action at low concentrations seems to meet the challenges. Conclusion: Phyto-active constituents, either alone or in combination with conventional antibiotics may be an effective approach to deal with global antimicrobial resistance. The efficacy of herbal therapy for decades suggests that bacteria, fungi, and viruses may have a reduced ability to adapt and resistance to these natural antimicrobial regimes.
Keywords: flavonoids